2004
DOI: 10.1038/ng1405
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in SLC6A19, encoding B0AT1, cause Hartnup disorder

Abstract: Hartnup disorder, an autosomal recessive defect named after an English family described in 1956 (ref. 1), results from impaired transport of neutral amino acids across epithelial cells in renal proximal tubules and intestinal mucosa. Symptoms include transient manifestations of pellagra (rashes), cerebellar ataxia and psychosis 1,2 . Using homozygosity mapping in the original family in whom Hartnup disorder was discovered, we confirmed that the critical region for one causative gene was located on chromosome 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
207
1
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 281 publications
(229 citation statements)
references
References 11 publications
6
207
1
3
Order By: Relevance
“…Furthermore, we and others [21,22] subsequently demonstrated that SLC6A19 constitutes a dominant transport activity for neutral amino acids in the kidney and intestine by showing that a malfunction of SLC6A19 results in severe neutral aminoaciduria, known as Hartnup disorder. Mouse slc6a19 is expressed in the outer cortex of the kidney and in the intestine [10], and therefore most likely corresponds to the transporter characterized in vesicle studies using kidney cortex or intestinal preparations.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…Furthermore, we and others [21,22] subsequently demonstrated that SLC6A19 constitutes a dominant transport activity for neutral amino acids in the kidney and intestine by showing that a malfunction of SLC6A19 results in severe neutral aminoaciduria, known as Hartnup disorder. Mouse slc6a19 is expressed in the outer cortex of the kidney and in the intestine [10], and therefore most likely corresponds to the transporter characterized in vesicle studies using kidney cortex or intestinal preparations.…”
Section: Introductionmentioning
confidence: 76%
“…We and others [21,22] have shown recently that mutations in the human B 0 AT1 (SLC6A19) cause Hartnup disorder. This indicates that B 0 AT1 is a major transport activity for neutral amino acids in the kidney and intestine.…”
Section: Physiological Significancementioning
confidence: 96%
See 2 more Smart Citations
“…SLC6A19 encodes the amino acid transporter B 0 AT1, which cotransports Na + and a broad range of neutral amino acids from the luminal compartment into the cells [4]. To date, about 20 mutations in SLC6A19, including missense, splicing, and small deletions and insertions, have been reported [5][6][7]. We recently examined a Korean boy with Hartnup disorder with novel mutations of the SLC6A19 gene.…”
Section: Introductionmentioning
confidence: 99%